Phosphorylation and isoform use in p120-catenin during development and tumorigenesis - Hong, Ji Yeon (Biochim Biophys Acta, 2015)
P120-catenin is essential to vertebrate development, modulating cadherin and small-GTPase functions, and growing evidence points also to roles in the nucleus. A complexity in addressing p120-catenin’s functions is its many isoforms, including optional splicing events, alternative points of translational initiation, and secondary modifications. In this review, we focus upon how choices in the initiation of protein translation, or the earlier splicing of the RNA transcript, relates to primary sequences that harbor established or putative regulatory phosphorylation sites. While certain p120 phosphorylation events arise via known kinases/ phosphatases and have defined outcomes, in most cases the functional consequences are still to be established. In this review, we provide examples of p120-isoforms as they relate to phosphorylation events, and thereby to isoform dependent protein-protein associations and downstream functions. We also provide a view of upstream pathways that determine p120’s phosphorylation state, thereby having an impact upon development and disease. Because other members of the p120 subfamily undergo similar processing and phosphorylation, as well as related catenins of the plakophilin subfamily, what is learned regarding p120 will by extension have wide relevance in vertebrates.